FASILITASI PERUMUSAN SUARA ANAK UNTUK PENDIDIKAN LOMBOK TENGAH - Affandi, Lalu Hamdian; Widiastuti, Sri Muliana; Annusapati, A. (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2025)
Democratic policy formulation needs data resources from first hand party. Children are the primary beneficiary of educational enterprises. Therefore, they need to be heard and involved in decision making processes. Current activity is an effort to explore and accommodate children’s voices in terms of their right fulfilment. Current activity was conducted in 2 days by inviting children’s representatives from each sub-district in Lombok Tengah. The activity was arranged by BAPPERIDA Kabupaten Lombok Tengah. Methods of activity are lecturing and presentation, focus group discussion, and pleno. Current activity produces 18 points of children’s voices which pertain to expectation for quality improvement of resources to support children’s rights and communication strengthening between children and parents, society, and government as policy maker. Conclusion can be drawn from this activity is children need for time and space for expressing their aspirations with ethics ways yet targeted at the problems they perceive.